USING OF ARTIFICIAL INTELLIGENCE ChatGPT AMONG HEALTH DEPARTMENT STUDENTS IN INDONESIA: A DESCRIPTIVE SURVEY STUDY - Susaldi Susaldi; Ruris Haristiani; Nur Al Marwah Asrul; Wa Ode Sri Asnaniar; Agus Purnama (UPT Penerbitan Universitas Jember, 2023)
Introduction: ChatGPT is a model machine learning created by OpenAI with the aim of autogenerating text. This model is designed to respond to questions or requests for information by generating relevant answers. ChatGPT is trained using very large text data, so it has the ability to produce a variety of responses. Aims: This study aims to describe the use of ChatGPT among students majoring in health at various universities in Indonesia.Method: The research method used is a descriptive study with a sample of 236 students. Result: (1) The age of the respondents is between 17-26 years: 31 male students (13.14%), 223 female students(86.86%), the most majors health is Nursing study program with 138 students (58.5%) ; (2) of the total sample, 122 respondents (51.7%) stated that they had never received information about ChatGPT, and 114 (48.3%) knew about this model; (3) 175 (74.2%) respondents have never used ChatGPT and 61 respondents (25.8%) have used it; (4) Intensity of use: 37 respondents (60.66%) used it several times a week, 13 (21.31%) used it several times a month, 9 (14.75%) use it every day and 2 (3.28%) were rarely use; (5) The use of ChatGPT were to find various information and to do college assignments; (6) 100% of respondents who have used ChatGPT stated that this model could replace Google Search Engine in presenting various information. Keyword: ChatGPT, Health Student.